Multivisceral Transplantation for Diffuse Portomesenteric Thrombosis: A Case Series. (July 2018) - Canovai, Emilio; Ceulemans, Laurens; De Hertogh, Gert; Hiele, Martin; Sainz-Bariga, Mauricio; Jochmans, Ina; Vanuytsel, Tim; Monbaliu, Diethard; Pirenne, Jacques
Abstract : Introduction: Multivisceral transplantation (MVTx) entails the en-bloc transplantation of almost the entire abdominal contents including stomach, duodenum, pancreas, liver and small bowel. For adults, indications for MVTx include slow growing abdominal tumors involving the mesenteric vessels, massive abdominal losses due to trauma or ischemic disease and diffuse portomesenteric thrombosis (DPMT). In the latter, DPMT will often lead to life-threatening upper GI bleeding. Furthermore, these patients often have an underlying liver cirrhosis requiring a liver transplantation. In these cases, portal revascularization is technically impossible without simultaneous replacement of the entire portal system. Aim: To study the results of multivisceral transplantation for diffuse portomesenteric thrombosis. Methods: A retrospective analysis from prospectively maintained database ITx patients transplanted from2000-2017 was performed and the MVTx patients were identified. Demographics, indication, donor characteristics, rejection episodes and survival were recorded. Results: 4 male patients underwent MVTx in this period out of a total of 19 ITx performed at our center(21%). Median age at time of transplantation was 45 (range: 23-47). The indication for MVTx was DMPT with recurrent life treating bleeding.Underlying causes where antiphospholipid syndrome, alcoholic cirrhosis, pancreatic neuroendocrine tumor and unknown in one patient. One patient had underlying liver failure and was hospitalized at time of transplantation. Median MELD score at time of transplantation was 13 (10-32). All patients received grafts from brain-dead donors (median age: 24.5 years). To reduce massive bleeding during exenteration, embolization of the superior mesenteric artery and the celiac trunk was performed to reduce perioperative bleeding, followed by en-bloc resection of native stomach, duodenum, pancreas, liver and bowel, and finally en-bloc transplantation of the corresponding organs. GI continuity was restored by oesophagogastrostomy proximally and ileo-colostomy distally. All patients received a protective double loop ileostomy for endoscopic surveillance. Patients received basiliximab induction followed by triple maintance therapy: tacrolimus, azathioprine and corticosteroids. There were 4 rejection episodes in 3 patients, 3 of which were treatable by increasing standard immunosuppression. One patient died 254 days after surgery due to invasive aspergillosis after a severe rejection. The 3 remaining patients are alive and are nutritionally independent (median follow-up 2.14 years). Conclusions: MVTx allows for complete treatment of diffuse portomesenteric thrombosis with good quality of life in patients who would otherwise die from severe bleeding. Coordination amongst the donor, embolization and implantation teams is crucial to keep blood loss and cold ischemia times as short as possible. Figure. No caption available. Figure. No caption available.